Developing the Al-Ghazali Learning Values Scale: Initial Evidence of Validity and Reliability among Online Learners - Pelita Hayati; Evi Afifah Hurriyati (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
Learning values play an important role in shaping students’ attitudes toward knowledge, discipline, and academic responsibility. Although Al-Ghazali’s educational philosophy provides a rich framework for value-based learning, empirical instruments designed to measure these values remain limited in contemporary educational research. This study aimed to examine the initial psychometric properties of the Al-Ghazali Learning Values Scale among students engaged in online learning. The instrument was developed based on key dimensions derived from Al-Ghazali’s educational thought, including sincerity in learning, academic ethics, self-reflection, perseverance in seeking knowledge, and the integration of knowledge with moral and spiritual purposes. The preliminary scale consisted of 28 items and was administered to 263 Muslim students enrolled in online learning programs. Item validity was examined using corrected item–total correlation, while internal reliability was assessed using Cronbach’s alpha coefficient. The results indicated that all items met the minimum validity criterion and demonstrated strong internal consistency, with a Cronbach’s alpha coefficient of 0.894. The Kaiser–Meyer–Olkin statistic also indicated excellent sampling adequacy. These findings provide preliminary empirical evidence supporting the feasibility of the Al-Ghazali Learning Values Scale as a tool for examining value-based learning within the context of contemporary educational research.